One dimensional AuAg nanostructures as anodic catalysts in ethylene glycol oxidation - Lyons, Michael; Gounko, Iouri; Morris, Michael (My University, 2020)
Direct alcohol fuel cells are highly promising as efficient power sources for various mobile and portable applications. However, for the further advancement of fuel cell technology it is necessary to develop new, cost-effective Pt-free electrocatalysts that could provide efficient alcohol oxidation and also resist cross-over poisoning. Here, we report new electrocatalytic materials for ethylene glycol oxidation, which are based on AuAg linear nanostructures. We demonstrate a low temperature tunable synthesis that enables the preparation of one dimensional (1D) AuAg nanostructures ranging from nanowires to a new nano-necklace-like structure. Using a two-step method, we showed that, by aging the initial reaction mixture at various temperatures, we produced ultrathin AuAg nanowires with a diameter of 9.2 - 2 and 3.8 - 1.6 nm, respectively. These nanowires exhibited a high catalytic performance for the electro-oxidation of ethylene glycol with remarkable poisoning resistance. These results highlight the benefit of 1D metal alloy-based nanocatalysts for fuel cell applications and are expected to make an important contribution to the further development of fuel cell technology.
PUBLISHED
Keywords: electro-oxidation; one dimensional (1D) AuAg nanostructures; fuel cell technology; electro-oxidation; one dimensional (1D) AuAg nanostructures; fuel cell technology; Nanoscience & Materials